Educational Needs of Nursing Students for Working in Addiction Counseling and Treatment Centers - Habibolah Rezaei; Ferdowsi Rahimi; Nikoo Yamani (مجله ایرانی آموزش در علوم پزشکی, 2018)
Introduction: Nurses must be equipped with scientific and practical competencies and skills in teaching drug abuse prevention and control as well as addiction treatment. Thus, this study aimed to determine the educational needs of nursing students for working in addiction counseling and treatment centers. Methods: This descriptive study was conducted in Isfahan in the 2015-16 academic year. The statistical population was comprised of faculty members of the nursing and midwifery school, physicians, nurses and the service recipients provided by addiction counseling and treatment centers. Using a three-round Delphi Technique, the data were collected by a valid and reliable researcher-made questionnaire and analyzed by means of descriptive statistics. Results: In the first, second and third rounds of Delphi Technique, 129 (out of 140), 79 (out of 80), and 20 (out of 20) people responded to the questionnaire respectively. Of the 150 educational needs that were identified, 69 were related to the cognitive domain, 39 to the emotional domain and 42 were related to the psychomotor domain. Conclusion: Most of the nursing students’ educational needs of nurses for working in addiction counseling and treatment centers were related to the cognitive and psychomotor domain. It is suggested that training courses be held for nursing students in relation to these needs and an educational package be developed accordingly.